1999
DOI: 10.1177/104063879901100203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR, Virus Isolation, and Indirect Fluorescent Antibody Staining in the Detection of Naturally Occurring Feline Herpesvirus Infections

Abstract: Cats with clinical signs suggestive of ocular infection with feline herpesvirus type 1 (FHV 1) and cats without such signs were assayed by 3 methods to detect FHV. Comparison of polymerase chain reaction (PCR), virus isolation, and indirect fluorescent antibody staining techniques for the detection of FHV demonstrated higher sensitivity of PCR in detecting this common infectious agent of cats. Compared with PCR, sensitivity and specificity for virus isolation was 49% and 100%, respectively, and those of indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 15 publications
2
96
2
3
Order By: Relevance
“…The cats were allowed to become adapted to their new surroundings for 1 month prior to beginning the study. To confirm that the cats were not previously infected with FHV-1, conjunctival swabs from each eye were tested via virus isolation a and PCR assay 7 ; results of an ELISA indicated that the cats were seronegative for anti-FHV-1 antibodies. 8,b A CBC and serum biochemical analyses were performed on each cat during the adaptation period and 10 days after initiation of medical treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The cats were allowed to become adapted to their new surroundings for 1 month prior to beginning the study. To confirm that the cats were not previously infected with FHV-1, conjunctival swabs from each eye were tested via virus isolation a and PCR assay 7 ; results of an ELISA indicated that the cats were seronegative for anti-FHV-1 antibodies. 8,b A CBC and serum biochemical analyses were performed on each cat during the adaptation period and 10 days after initiation of medical treatment.…”
Section: Methodsmentioning
confidence: 99%
“…shed virus under natural conditions, and even then, transmission to susceptible animals is not necessarily easily achieved [30,34]. More recent studies using PCR, including realtime PCR, have shown a higher sensitivity for detecting carriers, with a more prolonged presence of viral DNA in the secretions of infected cats [8,45,83,111,125,131,141,146,147]. Whilst such molecular techniques help identify carriers, the epidemiological significance of cats in which viral genome can be detected by PCR, but from which infectious virus cannot be isolated is not clear, as transmission studies have not been performed.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies on pathogen detection have compared sites for sampling (17) and methods of detection, including PCR, culture, virus isolation, and indirect immunofluorescence (1,2). Enigmatically, choosing a diagnostic method or sample site on the basis of sensitivity alone will increase detection in low-shedding carriers, without regard to true causation.…”
mentioning
confidence: 99%